Macromineral consumption by Pleurotus ostreatus var. Florida in different straws - Iossi, Matheus R. [UNESP]; Vieira, Wagner G. [UNESP]; Caitano, Cinthia E. C. [UNESP]; da Silva Alves, Lucas [UNESP]; Palú, Isabela de A. [UNESP]; Heirinchs, Reges [UNESP]; Pardo-Giménez, Arturo; Zied, Diego C. [UNESP] (National Library of Serbia, 2023)
Organic agricultural waste is successfully used in the production of mushrooms as it promotes the reuse of resources and increases food production. For the formulation of the substrate for Pleurotus spp. production, the availability of nutrients must be rigorously analyzed to assess whether supplementation is necessary. The aim of this paper was to evaluate the agronomic behavior of Pleurotus ostreatus var. Florida when grown on different straws and to analyze nutrient dynamics at the beginning and end of cultivation. Straws of rice, wheat and brachiaria were used as substrates without any supplementation. The yields, biological efficiency, number and weights of mushrooms were evaluated in two crop cycles. Rice straw provided a higher yield, better biological efficiency and a greater number of mushrooms in both cultures. Wheat straw showed intermediate results for the same variables. None of the substrates showed a significant difference for mushroom weight. In the first crop, only Mg and the number of mushrooms exhibited a positive correlation; in the second crop, only K and the yield of the 1st flush showed a positive correlation. With this study, it was possible to demonstrate that agricultural residues with higher levels of K increase P. ostreatus yield, and that Mg management affects the number of mushrooms for harvesting. The results will be a useful guide for efficient and sustainable mineral supplementation of the substrate.
Keywords: mushroom production; nutrients; oyster mushroom; straw degradation